On the options of Ukraine’s nuclear fuel cycle - Krasnorutskyy, V.S.; Kirsanova, O.S. (Вопросы атомной науки и техники, 2019)
The current Energy Strategy of Ukraine establishes that electricity production at NPPs in future retains at least approximately equivalent to that currently produced. How this could be accomplished is hidden in general statements, which also applies to the issues and challenges of the Nuclear Fuel Cycle. It is known that NFC is the key indicator that determines the economy of NE. The uncertainty about which NFC options need to be developed and which NFC stages and steps need to be implemented in the time perspective complicate making timely decisions. This paper presents a summary of the cost options for an open and closed NFC with WWER and CANDU reactors using the costs of stages currently accepted in the world. Існуюча стратегія розвитку атомної енергетики (АЕ) України означає, принаймні, збереження в подальшому обсягу виробництва електроенергії на АЕС приблизно еквівалентним виробляємому на сьогодні. Як це зробити, ховається в загальних формулюваннях, це стосується і рішення проблем і завдань з ядерного паливного циклу (ЯПЦ). Відомо, що ЯПЦ – це основний показник, що визначає економіку АЕ. Невизначеність бачення, які ЯПЦ необхідно розвивати, які стадії і етапи реалізовувати в часовій перспективі, ускладнює прийняття своєчасних рішень. В узагальнюючому вигляді представлені оцінки варіантів витрат для відкритого і закритого ЯПЦ з реакторами типу ВВЕР і CANDU, з використанням витрат по етапам, що приймаються на сьогодні в світі. Существующая стратегия развития атомной энергетики (АЭ) Украины обозначает, по крайней мере, сохранение в дальнейшем объема производства электроэнергии на АЭС примерно эквивалентным производимому на сегодня. Как это сделать, скрывается в общих формулировках, это касается и решения проблем и задач по ядерному топливному циклу (ЯТЦ). Известно, что ЯТЦ – это основной показатель, определяющий экономику АЭ. Неопределенность видений, какие ЯТЦ необходимо развивать, какие стадии и этапы реализовывать во временной перспективе, затрудняет принятие своевременных решений. В обобщающем виде представлены оценки вариантов затрат ЯТЦ с реакторами типа ВВЭР и CANDU для открытого и закрытого циклов с использованием затрат по этапам, принимаемым на сегодня в мире.